Perbandingan Kinerja UKM Kluster Dan Non Kluster Di Kota Bengkulu - Tri Putri, Novi (Jurnal Ekonomi Kuantitatif Terapan, 2015)
Location is an important factor for a firm to grow. Firms will have many advantages if they were located in a cluster. This article will discuss about the factors that used to point the SME location of the special product in Bengkulu by using discriminant analysis. Generally, discriminant model that used have a good prediction ability, with a true prediction more than 78% cases. There are five different variable that found as predictors of the location; the amount of the labor, the government rules , the education of the businessman, source of the product supply, and capital investment. Based on the range of the performance, the ventures in non-cluster location show better performance than the ventures in cluster location.
Keywords: cluster; SME; special product; discriminant analysis